Perception of undergraduate medical students on integration of radiological anatomy for pre-clinical teaching / Reshma Mohamed Ansari - Reshma , Mohamed Ansari (2021)
Integration is the way forward to enable accommodation of the ever-expanding content in medical education. While revising the curriculum, stakeholders’ perception aids to tailor a curriculum matching their needs. Radiological anatomy (RA) is an integrated discipline of topographical, cross-sectional anatomy with radiological representation of structural anatomy. Though RA has been widely incorporated in most of the medical curricula, there is a dearth of standardization in terms of student learning time (SLT), content and teachers. This study was planned to record the perception of MBBS students on RA teaching in pre-clinical years in University of Cyberjaya, Malaysia. A modified, piloted and validated questionnaire was administered to year 1 to year 5 MBBS students through Google forms. Data received from 405 students was analysed using SPSS version 25. Though the unanimous response indicated adequate SLT, year 3 students (62%) felt that the current RA teaching is too little for them in their year of study. Radiologists and anatomists had a different approach while teaching RA. Students expressed that RA taught as practical sessions, problem-based learning (PBL) sessions and clinical correlation (CC) sessions are more effective rather than selfdirected learning. As for the content, pre-clinical students preferred limbs, head and neck and brain to comprehend topographical anatomy. On the contrary, clinical students preferred thorax and abdomen as relevant content for practise. X-ray and computed tomography (CT) were the most preferred radiological modalities due to their availability and feasibility. As an overall measure to improve RA teaching students suggested teaching-learning methods that encompass their active learning, modules with films and sound explanations, increase in SLT and radiologists as future RA teachers. The student responses provided an insight into the changes to be implemented and directions for future research.